Housing Policies in Maine: A Historical Overview - O’Hara, Frank (Maine Policy Review, 1999)
Frank O’Hara traces the evolution of Maine’s housing policies from Maine’s settlement after the Revolutionary War to the current era, where concerns about sprawl and the preservation of communities have come to the fore. In doing so, O’Hara points out that the approach to housing has always reflected more than a desire to ensure every person has adequate shelter. Rather, it reflects core values and beliefs about society, our sense of beauty, and our relationship to the environment and one another. O’Hara urges policymakers to keep these broader constructs in mind when addressing Maine’s future housing needs. As history shows, Maine’s housing policies have formed the vital core of larger efforts to create vibrant and diverse community centers.
Keywords: Maine housing policy; Maine history; urban renewal; affordable housing; sprawl